Smartphone-microfluidic fluorescence imaging system for studying islet physiology - Yu, Xiaoyu; Xing, Yuan; Zhang, Yiyu; Zhang, Pu; He, Yi; Ghamsari, Farid; Ramasubramanian, Melur K.; Wang, Yong; Ai, Huiwang; Oberholzer, Jose (Frontiers in Endocrinology, 2022)
Smartphone technology has been recently applied for biomedical image acquisition and data analysis due to its high-quality imaging capability, and the flexibility to customize multi-purpose apps. In this work, we developed and characterized a smartphone-microfluidic fluorescence imaging system for studying the physiology of pancreatic islets. We further evaluated the system capability by performing real-time fluorescence imaging on mouse islets labelled with either chemical fluorescence dyes or genetically encoded fluorescent protein indicators (GEFPIs). Our results showed that the system was capable of analyzing key beta-cell insulin stimulator-release coupling factors in response to various stimuli with high-resolution dynamics. Furthermore, the integration of microfluidics allowed high-resolution detection of insulin secretion at single islet level. When compared to the combination of conventional fluorescence microscopes and macro islet perifusion apparatus, the system has the advantages of low cost, portable, and easy to operate. With all of these features, we envision that this smartphone-microfluidic fluorescence imaging system can be applied to study islet physiology and clinical applications.